2009
DOI: 10.1038/sj.bjc.6605107
|View full text |Cite
|
Sign up to set email alerts
|

Type IV collagen is a tumour stroma-derived biomarker for pancreas cancer

Abstract: BACKGROUND: Pancreas cancer is a dreaded disease with high mortality, despite progress in surgical and oncological treatments in recent years. The field is hampered by a lack of good prognostic and predictive tumour biomarkers to be used during follow-up of patients. METHODS: The circulating level of type IV collagen was measured by ELISA in pancreas cancer patients and controls. The expression pattern of type IV collagen in normal pancreas, pancreas cancer tissue and in pancreas cancer cell lines was studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
5
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 29 publications
(26 reference statements)
3
70
5
2
Order By: Relevance
“…This finding was unexpected as other studies had shown increased progression and poor survival in cases with high type IV collagen tissue expression (16,17,30). Our data were the result of a blinded evaluation of the type IV collagen expression.…”
Section: Nonmalignant Epithelium Invasive Frontcontrasting
confidence: 47%
See 4 more Smart Citations
“…This finding was unexpected as other studies had shown increased progression and poor survival in cases with high type IV collagen tissue expression (16,17,30). Our data were the result of a blinded evaluation of the type IV collagen expression.…”
Section: Nonmalignant Epithelium Invasive Frontcontrasting
confidence: 47%
“…As mentioned previously, the exact mechanism underlying the formation of the analyte is largely unknown. Previous studies have suggested that proteolysis and desmoplasia as a result of tissue remodeling are the responsible mechanisms (15,17). Patients with fibrotic and cirrhotic liver disorders also have increased levels of circulating type IV collagen (27,29), indicating that the mechanism for type IV collagen release is not exclusively cancer specific.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations